Effects of underweight, overweight, and obesity on the body growth of preschoolers - Chen, Jiebo; Luo, Dongmei; Fan, Xue (Frontiers in Public Health, 2024)
ObjectiveThis study aimed to investigate the impact of underweight, overweight, and obesity on the growth and development of preschoolers by comparing body shape characteristics across different weight statuses.MethodsA total of 729 preschoolers (5.2 ± 0.83 years, 53.8% boys) from three kindergartens were assessed for 11 different body shape measurements. Two-way ANOVA was employed to examine BMI variations across different ages and sexes. Discriminant analysis was utilized to identify body shape measurements correlated with BMI, and one-way ANOVA was conducted to compare the body shape differences among preschoolers with varying BMI.Results(1) There was no significant interaction effect of gender and age on BMI (F = 1.602, p = 0.173). Additionally, neither the main effect of age (F = 1.461, p = 0.228) nor the main effect of sex (F = 0.905, p = 0.345) was significant. (2) The results of the stepwise discriminant analysis showed that chest circumference, calf length, calf circumference, foot length, and width between greater trochanters entered the discriminant model, with the three discriminant functions explaining 95.8, 3.1, and 1.1% of variance, respectively. (3) Compared to their normal-weight counterparts, obese preschoolers displayed significantly larger measurements in chest circumference, width between greater trochanters, calf circumference, calf length, and foot length (p < 0.05). Overweight preschoolers also exhibited larger chest and calf circumferences, and width between greater trochanters (p < 0.05), while underweight children showed lagging development in various body shape measurements (p < 0.05).ConclusionVariations in BMI were significantly correlated with preschoolers’ body shape which included chest circumference, calf length, calf circumference, foot length, and the distance between the greater trochanters. Overweight and obese preschoolers experienced faster body growth; conversely, underweight preschoolers often showed delayed growth. This underscores that the underweight group also merits attention and concern.